Synthesized of Some New 1-H-3-(2’-Hydroxy-5’-Methyl-4’,6’-Dibromophen-1’-yl)-5-Sustituted Phenyl-2-Pyrazoline and Related Compounds and Their Antibacterial Activity - Naik, S.M.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Several new 1-H-3-(2"-hydroxy-5"-methyl-4"-6´-dibromophen-1"-yl)-5-substituted phenyl-2-pyrazolines [2(a-j)] have been prepared by the reactions of 1-(2´-hydroxy-5´-methyl-4´,6´-dibromophen-1´-yl)-3-substituted phenyl-2 propen-1 ones [1(a-j)]with hydrazine hydrate in ethanol. Their N-substituted derivatives [3(a-j), 4(a-j)] have been prepared by acetylation and benzoylation. They have been screened against a few microorganisms for antibacterial activities.